1998
DOI: 10.1128/jcm.36.8.2214-2219.1998
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Staphylococcus schleiferi Wound Infections: Strain Characterization by Randomly Amplified Polymorphic DNA Analysis, PCR Ribotyping, Conventional Ribotyping, and Pulsed-Field Gel Electrophoresis

Abstract: Within a 1-year period, six surgical-site infections (SSI) caused by Staphylococcus schleiferi were observed in the department of cardiac surgery of Ignatius Hospital, Breda, The Netherlands. Since outbreaks caused by this species of coagulase-negative staphylococci have not been described before, an extensive environmental survey and a case control study were performed in combination with molecular typing of the causative microorganism in order to identify potential sources of infection. Variability, as detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 36 publications
2
25
1
2
Order By: Relevance
“…These findings fulfilled the Duke clinical criteria for definite endocarditis (4). A recent paper (9) suggested that endocarditis due to S. schleiferi has been previously reported. The references given were two that reported blood culture isolates of S. schleiferi.…”
supporting
confidence: 63%
“…These findings fulfilled the Duke clinical criteria for definite endocarditis (4). A recent paper (9) suggested that endocarditis due to S. schleiferi has been previously reported. The references given were two that reported blood culture isolates of S. schleiferi.…”
supporting
confidence: 63%
“…The phenotypic similarities of S. schleiferi with S. aureus, in addition to the positive coagulase test, have resulted in misidenti¢cation of these species as S. aureus (2,5). Biochemical markers, which can be used to identify the subspecies of S. schleiferi as unique from S. aureus, include their limited fermentation of maltose, lactose, mannitol, sucrose, and turanose (2,5,7 ). The Staph-Plus test initially used in identi¢cation, which simultaneously detects both clumping factor and protein A, cannot help to distinguish subsp.…”
Section: Discussionmentioning
confidence: 99%
“…schleiferi from subsp. coagulans (6,7 ). As a result of these subtle variations, misidenti¢cation is common.…”
Section: Discussionmentioning
confidence: 99%
“…There is an ever‐present risk of MRS exposure for patients and humans in a veterinary hospital. Staphylococcus aureus and S. schleiferi are well‐documented human pathogens, so potential for cross‐species transmission exists. Although not considered to be a human pathogen, S. pseudintermedius can be detected by culture of nasal swabs from dog owners and veterinarians .…”
Section: Veterinary Hospital Infection Controlmentioning
confidence: 99%